Clinical effectiveness of VIA and colposcopy based management of cervical intraepithelial neoplasia - Jesmin, Zannatul Ferdous; Khanam, Afroza; Saha, Eti; Hossain, Md Mokter (Bangladesh Medical Journal Khulna, 2015)
Cervical cancer develops from early precancerous lesion known as cervical intraepithelial neoplasia (CIN). Khulna Medical college Hospital provides primary screening for preventing cervical cancer and a secondary referral centre for management of CIN by colposcopy. Primary objective of this study was to do an audit between January 2012 to February 2014 to update clinical efficacy of colposcopy based diagnosis, treatment and follow up of 510 CIN cases and also to document any shortcomings in existing services and suggestion for early rectification. Colposcopic findings in our study group were: 309(60.6%) cases were CIN-1, 124 (24.3%) cases was CIN II, and 49 (9.6%) cases were CIN III. Suspicious of invasive lesion was in 7 (1.4%) abnormal looking cervix and biopsy was done in 21(4.1%). Treatment procedure was done with individualization of cases and options were cold coagulation, Loop electrosurgical excision procedure (LEEP), hysterectomy, biopsy and post treatment follow up. Histopathological diagnosis was documented in 387 cases, where CINI was found in 161 (31.6%), CIN II in 92 (18%), CIN III in 26 (5.1%), non specific Inflammatory cervicitis in 87(17.1%), Squamous cell carcinoma in 15(2.9%), abnormalities consistent with koilocytic atypia in 6 (12%) and reports missed in 123 (24.1%). Cases results showed Positive predictive value (PPV) of 53% and 68% respectively for low grade (CIN I) and high grade lesion (CIN II, III). 481 patient were eligible for post treatment follow up but only 99 (20.5%) patient came and among them 74 (74.7%) were colposcopically negative, 25 (25.2%) had residual CIN and Risk Ratio (RR) was 0.25. Colposcopy is gold standard for diagnosis of CIN but our screening program is opportunistic and far way from population based. Histopathological correlation were often inaccurate with colposcopic diagnosis in practice and about one third case reports were missed. Majority of women did not complete follow up protocol. Residual or recurrent CIN lesion in dropped out cases would be a concern in near future. DOI: http://dx.doi.org/10.3329/bmjk.v47i1-2.22557 Bang Med J (Khulna) 2014; 47 : 16-20